School Programs in Speech-Language Pathology : Organization and Delivery, Sixth Edition. - Blosser, Jean L. (Plural Publishing, Incorporated, 2019)
This text provides a foundation for understanding where speech-language pathology (SLP) programs fit within the school organization. SLPs will be motivated to collaborate with colleagues, lead discussions about the link between communication and learning, and introduce innovative models for delivering services. School Programs encourages SLPs to embrace their positions on school teams, share knowledge to make services educationally relevant and help children reach their highest potential.